A lithium-rich manganese-based positive electrode material, a preparation method and application thereof, a composite positive electrode and a solid-state battery
Patent Information
- Application Number
- CN202611424126.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]然而,单晶富锂锰基正极材料在实际应用中仍存在以下技术难题:单晶材料因晶格完整、无晶界通道,导致Li2MnO3相难以活化,Li+扩散速率低,同时单晶材料比表面积小,与固态电解质的固-固界面接触效果差,使得其实际比容量大幅降低(通常仅180~220mAh/g),无法充分发挥富锂锰基材料的高容量优势,倍率性能不佳,难以满足固态电池高容量、高功率的应用需求
本发明能够同时保留单晶材料结构稳定性优势、同时解决单晶材料活化难和界面接触差问题,通过第一烧结制备单晶基体,稳定单晶结构,通过喷雾干燥将包覆剂均匀负载于单晶颗粒表面并经第二烧结形成包覆层,提高材料界面离子电导率并改善固-固接触,最后添加LiOH作为粘接剂并经加压处理和第三烧结,使单晶颗粒之间形成晶界、团聚为二次颗粒,增加Li+扩散通道并缩短扩散距离,从而有效活化Li2MnO3相,最终使材料在保留单晶结构稳定性的同时,显著提高放电比容量、循环稳定性和倍率性能;本发明以Mo6+、Nb5+、W6+、Ta5+等高价、大半径阳离子为掺杂剂,作为体相掺杂,烧结形成单晶形貌,F-等阴离子替代晶格中O位和过渡金属位置,提高晶格稳定性,进而提高材料循环保持率。
Smart Images

Figure CN123017947A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-rich manganese-based cathode material preparation and solid-state battery application technology, specifically to a lithium-rich manganese-based cathode material, its preparation method and application, composite cathode, and solid-state battery. Background Technology
[0002] Lithium-rich manganese-based cathode materials have become highly promising cathode materials for solid-state batteries due to their advantages such as extremely high specific capacity (>250mAh / g), low cost, and environmental friendliness. Based on morphology, lithium-rich manganese-based cathode materials can be divided into two types: monocrystalline and polycrystalline. Among them, monocrystalline lithium-rich manganese-based materials are considered ideal for solid-state batteries because they have complete single grains, no grain boundary defects, excellent structural stability, low volumetric deformation rate, small voltage drop, and fewer side reactions with solid electrolytes.
[0003] However, single-crystal lithium-rich manganese-based cathode materials still face the following technical challenges in practical applications: Due to the complete lattice and lack of grain boundary channels, the Li₂MnO₃ phase is difficult to activate in single-crystal materials, and Li… + The low diffusion rate and small specific surface area of the single crystal material result in poor solid-solid interface contact with the solid electrolyte, which significantly reduces its actual specific capacity (typically only 180~220mAh / g). This makes it impossible to fully utilize the high capacity advantage of lithium-rich manganese-based materials, resulting in poor rate performance and difficulty in meeting the application requirements of high capacity and high power in solid-state batteries.
[0004] To address the aforementioned issues, current technologies for modifying lithium-rich manganese-based cathode materials primarily focus on doping, coating, or crystal structure control. No technology has yet been developed that can simultaneously achieve the structural stability of single-crystal materials and the high capacity of polycrystalline materials. Therefore, developing a lithium-rich manganese-based cathode material with high capacity and excellent rate performance has become a pressing technical challenge in this field. Summary of the Invention
[0005] In view of this, the purpose of this invention is to provide a lithium-rich manganese-based cathode material, its preparation method and application, composite cathode, and solid-state battery. This invention prepares a single-crystal matrix through a first sintering process to stabilize the single-crystal structure. A coating agent is uniformly loaded onto the surface of the single-crystal particles through spray drying, followed by a second sintering to form a coating layer, improving the interfacial ionic conductivity and solid-solid contact. Finally, LiOH is added as a binder, and after pressure treatment and a third sintering, grain boundaries are formed between the single-crystal particles, agglomerating them into secondary particles, increasing the Li content. + The diffusion channels are expanded and the diffusion distance is shortened, thereby effectively activating the Li2MnO3 phase. Ultimately, the material retains the stability of the single crystal structure while significantly improving the discharge specific capacity, cycle stability and rate performance.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a lithium-rich manganese-based cathode material, comprising the following steps: The precursor, lithium salt and dopant are mixed and then subjected to a first sintering to obtain lithium-rich manganese-based sintered powder. The dopant includes one or more of ZrO2, TiO2, Al2O3, MgO, Co3O4, MoO3, Nb2O5, WO3, Ta2O5, NH4F, LiPO3, and Li2SO4; The lithium-rich manganese-based sintered powder and the coating agent are mixed and then spray-dried and sintered sequentially to obtain lithium-rich manganese-based bis-sintered powder; the coating agent includes a fast ion conductor material. The lithium-rich manganese-based sintered powder and LiOH were mixed and then subjected to pressure treatment and a third sintering process to obtain the lithium-rich manganese-based cathode material.
[0007] Preferably, the dopant element in the dopant includes one or more of Zr, Ti, Al, Mg, Co, Mo, Nb, W, Ta, F, P and S, and the molar amount of each dopant element in the dopant independently accounts for 0.03 to 3% of the total molar amount of transition metal elements in the precursor.
[0008] Preferably, the first sintering includes a first stage sintering, a second stage sintering, and a third stage sintering performed sequentially. The temperature of the first stage sintering is 450~550℃ and the holding time is 3~6h. The temperature of the second stage sintering is 800~950℃ and the holding time is 8~12h. The temperature of the third stage sintering is 1000~1100℃ and the holding time is 3~6h.
[0009] Preferably, the fast ion conductor material is a mixture of NH4H2PO4 and LiOH, a mixture of SiO2 and LiOH, or a mixture of NH4VO3 and LiOH; the amount of coating agent added is 0.05~1% of the mass of the lithium-rich manganese-based sintered powder; the spray drying temperature is 110~130℃; the second sintering temperature is 500~650℃, and the holding time is 4~7h.
[0010] Preferably, the mass ratio of the lithium-rich manganese-based di-calcined powder to LiOH is 150~200:1; the pressure of the pressurization treatment is 2~5T, and the holding time is 2~5min; the temperature of the third sintering is 500~600℃, and the holding time is 4~7h.
[0011] Preferably, the precursor has the general formula Mn x M y(OH)2, wherein 0.5 < x < 1, 0 < y < 0.5, x + y = 1, and M is Ni and / or Co; the molar ratio of the precursor to the lithium salt is 1:1.3 to 1:1.6, and the molar ratio is calculated based on the total molar amount of transition metal elements in the precursor and the molar amount of lithium elements in the lithium salt.
[0012] The present invention also provides a lithium-rich manganese-based cathode material prepared by the preparation method described in the above technical solution.
[0013] The present invention also provides the application of the lithium-rich manganese-based cathode material described in the above technical solution in solid-state batteries.
[0014] The present invention also provides a composite cathode comprising the lithium-rich manganese-based cathode material, halide solid electrolyte, and conductive agent described in the above technical solution, wherein the halide solid electrolyte comprises Li3InCl6.
[0015] The present invention also provides a solid-state battery comprising the composite positive electrode, sulfide solid electrolyte and negative electrode described in the above technical solution, wherein the sulfide solid electrolyte comprises Li6PS5Cl.
[0016] This invention provides a method for preparing a lithium-rich manganese-based cathode material, comprising the following steps: The precursor, lithium salt and dopant are mixed and then subjected to a first sintering to obtain lithium-rich manganese-based sintered powder. The dopant includes one or more of ZrO2, TiO2, Al2O3, MgO, Co3O4, MoO3, Nb2O5, WO3, Ta2O5, NH4F, LiPO3, and Li2SO4; The lithium-rich manganese-based sintered powder and the coating agent are mixed and then spray-dried and sintered sequentially to obtain lithium-rich manganese-based bis-sintered powder; the coating agent includes a fast ion conductor material. The lithium-rich manganese-based sintered powder and LiOH were mixed and then subjected to pressure treatment and a third sintering process to obtain the lithium-rich manganese-based cathode material.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention simultaneously retains the structural stability advantages of single-crystal materials while solving the problems of difficult activation and poor interfacial contact. A single-crystal matrix is prepared through a first sintering process to stabilize the single-crystal structure. A coating agent is uniformly loaded onto the surface of the single-crystal particles through spray drying, followed by a second sintering to form a coating layer, improving the interfacial ionic conductivity and solid-solid contact. Finally, LiOH is added as a binder, and after pressure treatment and a third sintering, grain boundaries are formed between the single-crystal particles, agglomerating them into secondary particles and increasing the Li content. +The diffusion channel is shortened, thereby effectively activating the Li2MnO3 phase, ultimately enabling the material to significantly improve discharge specific capacity, cycle stability, and rate performance while retaining the stability of the single-crystal structure; this invention uses Mo 6+ 、Nb 5+ W 6+ Ta 5+ High-valence, large-radius cations are used as dopants for bulk doping, and sintering is performed to form a single crystal morphology. - Anions replace O sites and transition metal sites in the crystal lattice, improving lattice stability and thus increasing the material's cycle retention rate.
[0018] The present invention also provides a lithium-rich manganese-based cathode material prepared by the preparation method described in the above technical solution. Data from the embodiments of the present invention show that the discharge capacity of the lithium-rich manganese-based cathode material prepared by the present invention is 267.8~274.8 mAh / g, the initial coulombic efficiency is 87.5%~90.8%, and the 100-cycle retention rate is 91.5%~94.9%.
[0019] The present invention also provides the application of the lithium-rich manganese-based cathode material described in the above technical solution in solid-state batteries.
[0020] The present invention also provides a composite cathode comprising the lithium-rich manganese-based cathode material, halide solid electrolyte, and conductive agent described in the above technical solution, wherein the halide solid electrolyte comprises Li3InCl6.
[0021] This invention also provides a solid-state battery comprising the composite positive electrode, sulfide solid electrolyte, and negative electrode described in the above technical solution, wherein the sulfide solid electrolyte comprises Li6PS5Cl. The lithium-rich manganese-based positive electrode material and the halide solid electrolyte are combined and used at the positive electrode, which can protect the structural stability of the lithium-rich manganese-based positive electrode material under high voltage. The electrolyte is a sulfide solid electrolyte, and the halide on the positive electrode side and the sulfide on the electrolyte side work synergistically to reduce the influence of the space charge layer, thereby obtaining a higher discharge specific capacity. Attached Figure Description
[0022] Figure 1 The charge-discharge curves of the samples in Examples 1 and 3, and Comparative Examples 1 to 4 at 0.1C are shown. Figure 2 The specific capacity retention curves of the samples in Examples 1 and 3 and Comparative Examples 1 to 4 at 1C discharge are shown. Figure 3 SEM image of the sample in Example 1; Figure 4 The image shows the SEM image of the sample in Comparative Example 3. Detailed Implementation
[0023] This invention provides a method for preparing a lithium-rich manganese-based cathode material, comprising the following steps: The precursor, lithium salt and dopant are mixed and then subjected to a first sintering to obtain lithium-rich manganese-based sintered powder. The dopants include ZrO2, TiO2, Co3O4, MoO3, Nb2O5, WO3, Ta2O5, NH4F, and LiPO4. 3、 and one or more of Li2SO4; The lithium-rich manganese-based sintered powder and the coating agent are mixed and then spray-dried and sintered sequentially to obtain lithium-rich manganese-based bis-sintered powder; the coating agent includes a fast ion conductor material. The lithium-rich manganese-based sintered powder and LiOH were mixed and then subjected to pressure treatment and a third sintering process to obtain the lithium-rich manganese-based cathode material.
[0024] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0025] The present invention involves mixing a precursor, a lithium salt, and a dopant, followed by a first sintering process to obtain a lithium-rich manganese-based sintered powder.
[0026] In this invention, the preferred general formula of the precursor is Mn. x M y (OH)2, wherein 0.5 < x < 1, 0 < y < 0.5, x + y = 1, M is preferably Ni and / or Co, the median particle size of the precursor is preferably 1.5~3.5 μm, the lithium salt preferably includes lithium carbonate or lithium hydroxide; the molar ratio of the precursor to the lithium salt is preferably 1:1.3~1:1.6, the molar ratio being calculated based on the total molar amount of transition metal elements in the precursor and the molar amount of lithium element in the lithium salt.
[0027] In this invention, the dopant includes one or more of ZrO2, TiO2, Co3O4, MoO3, Nb2O5, WO3, Ta2O5, NH4F, LiPO3, and Li2SO4, more preferably ZrO2, MoO3, Nb2O5, WO3, or NH4F. The doping element in the dopant preferably includes one or more of Zr, Ti, Al, Mg, Co, Mo, Nb, W, Ta, F, P, and S. The molar amount of each doping element in the dopant preferably independently accounts for 0.03-3% of the total molar amount of transition metal elements in the precursor, specifically 0.05%, 0.1%, 0.5%, 1%, or 2%. The dopant contains Mo... 6+ 、Nb 5+ W 6+ Ta 5+ High-valence, large-radius cations are used as bulk dopants, and sintering is performed to form a single crystal morphology. -Anions replace O sites and transition metal sites in the crystal lattice, improving lattice stability and thus increasing the material's cycle retention rate.
[0028] The present invention preferably uses a high-speed mixer to mix the precursor, lithium salt and dopant. The present invention does not have any special limitation on the high-speed mixer, and any high-speed mixer well known to those skilled in the art can be used. The mixing speed is preferably 2000~3000 r / min, and the mixing time is preferably 30~40 min.
[0029] In this invention, the first sintering preferably includes a first-stage sintering, a second-stage sintering, and a third-stage sintering performed sequentially. The temperature of the first-stage sintering is preferably 450~550℃, the holding time is preferably 3~6h, and the temperature is preferably increased from room temperature to the first-stage sintering temperature at a heating rate of 2℃ / min. The first-stage sintering can remove carbon dioxide from lithium carbonate and bound water from the precursor.
[0030] In this invention, the temperature is preferably increased from the first-stage sintering temperature to the second-stage sintering temperature at a heating rate of 5°C / min. The second-stage sintering temperature is preferably 800~950°C, and the holding time is preferably 8~12h. A solid-state reaction occurs during the second-stage sintering process to generate a lithium-rich manganese-based polycrystalline material.
[0031] In this invention, the temperature is preferably increased from the second-stage sintering temperature to the third-stage sintering temperature at a heating rate of 5°C / min. The third-stage sintering temperature is preferably 1000~1100°C, and the holding time is preferably 3~6 hours. During the third-stage sintering process, the primary particles of the polycrystalline material melt together, and the secondary polycrystalline spheres break into single crystals.
[0032] In this invention, after the first sintering is completed, the obtained material is preferably crushed to obtain the lithium-rich manganese-based sintered powder, and the median particle size of the lithium-rich manganese-based sintered powder is preferably 2~4μm.
[0033] After obtaining lithium-rich manganese-based mono-calcined powder, the present invention mixes the lithium-rich manganese-based mono-calcined powder with a coating agent and then performs spray drying and second sintering sequentially to obtain lithium-rich manganese-based di-calcined powder.
[0034] In this invention, the coating agent comprises a fast ion conductor material, preferably comprising a mixture of NH4H2PO4 and LiOH, a mixture of SiO2 and LiOH, or a mixture of NH4VO3 and LiOH; the mass ratio of NH4H2PO4 to LiOH in the NH4H2PO4 and LiOH mixture is preferably 0.91:1 to 1.05, the mass ratio of SiO2 to LiOH in the SiO2 and LiOH mixture is preferably 2.38:1 to 1.05, and the mass ratio of NH4VO3 to LiOH in the NH4VO3 and LiOH mixture is preferably 2.79:1 to 1.05. The LiOH in the fast ion conductor material is preferably used in the form of LiOH·H2O. All the above mass ratios are calculated in terms of LiOH·H2O. The amount of coating agent added is preferably 0.05% to 1% of the mass of the lithium-rich manganese-based calcined powder, specifically 0.08%, 0.1%, 0.2%, 0.5%, or 0.8%.
[0035] In this invention, the coating agent is preferably dissolved in deionized water to form a coating agent solution for use. The mass ratio of the deionized water to the lithium-rich manganese-based monocalcined powder is preferably 0.8 to 3:1, specifically 1.2:1, 1.5:1, or 1.8:1. Preferably, the lithium-rich manganese-based monocalcined powder and the coating agent solution are mixed under stirring conditions. The stirring temperature is preferably 40 to 60°C, specifically 45°C, 50°C, or 55°C, and the stirring time is preferably 2 hours.
[0036] In this invention, the spray drying temperature is preferably 110~130℃, specifically 115, 120 or 125℃. Spray drying can achieve rapid drying of materials, so that the coating agent is uniformly loaded on the surface of lithium-rich manganese-based calcined powder particles.
[0037] In this invention, the preferred sintering temperature is 500-650℃, specifically 550, 600, or 630℃, and the preferred holding time is 4-7 hours. The second sintering is preferably carried out in an air atmosphere, preferably at a heating rate of 2℃ / min from room temperature to the second sintering temperature. During the second sintering process, a fast ion conductor coating layer is generated in situ. NH4H2PO4 and LiOH·H2O react to generate Li3PO4, NH4VO3 and LiOH·H2O react to generate LiVO3, and SiO2 and LiOH·H2O react to generate Li2SiO3. The fast ion conductor coating layer has high ionic conductivity, which can effectively improve the conductivity of lithium-rich manganese-based materials and enhance the interfacial Li... + Transmission efficiency.
[0038] After obtaining lithium-rich manganese-based di-calcined powder, the present invention mixes the lithium-rich manganese-based di-calcined powder with LiOH and then performs pressure treatment and third sintering sequentially to obtain the lithium-rich manganese-based cathode material.
[0039] In this invention, the mass ratio of the lithium-rich manganese-based dicalcined powder to LiOH is preferably 150-200:1, and the LiOH is preferably LiOH·H2O, specifically 160:1, 180:1 or 190:1. The LiOH·H2O acts as a binder between single crystal particles, promoting the adhesion and fusion between single crystal particles to form agglomerates.
[0040] The present invention preferably uses a high-speed mixer to mix the lithium-rich manganese-based dicalcined powder and LiOH, wherein the mixing speed is preferably 3000 r / min and the mixing time is preferably 40 min.
[0041] In this invention, after the mixing is completed, the mixture is preferably placed in a pressure vessel for pressurization. The pressure of the pressurization is preferably 2 to 5T, specifically 2.5, 3, 3.5, 4 or 4.5T, and the pressure holding time is preferably 2 to 5 minutes, specifically 2.5, 3, 3.5, 4 or 4.5 minutes. The diameter of the pressure vessel is preferably 9 mm.
[0042] In this invention, the preferred temperature for the third sintering is 500-600℃, specifically 520, 550, or 580℃, and the preferred holding time is 4-7 hours. The third sintering is preferably carried out under pressure, with the pressure preferably being 2-5T, specifically 2.5, 3, 3.5, 4, or 4.5T, and the preferred holding time being 2-5 minutes, specifically 2.5, 3, 3.5, 4, or 4.5 minutes. Under the synergistic effect of pressure and the LiOH binder, the single crystal particles adhere and fuse during the third sintering process, agglomerating into secondary particles and forming artificial grain boundaries, thus improving ionic conductivity. This structure retains the stable lattice structure of the single crystal particles while providing abundant Li through the artificial grain boundaries. + The diffusion channel shortened the Li + The diffusion distance is increased, thereby effectively activating the Li2MnO3 phase and significantly improving the discharge specific capacity of the material.
[0043] In this invention, the temperature of the third sintering is preferably not higher than the temperature of the second sintering, so as to avoid over-sintering or structural damage of the fast ion conductor coating layer formed in the second sintering step due to excessive temperature, and to ensure the integrity of the coating layer and its ion conduction function.
[0044] The present invention preferably raises the temperature from room temperature to the third sintering temperature at a heating rate of 2°C / min. The third sintering is preferably performed in an air atmosphere.
[0045] Preferably, the obtained third sintered material is ground and sieved, and the collected material is the lithium-rich manganese-based cathode material. The present invention does not specifically limit the grinding and sieving methods; methods well known to those skilled in the art can be used.
[0046] The present invention also provides a lithium-rich manganese-based cathode material prepared by the preparation method described in the above technical solution.
[0047] The present invention also provides the application of the lithium-rich manganese-based cathode material described in the above technical solution in solid-state batteries.
[0048] The present invention also provides a composite cathode, which includes the lithium-rich manganese-based cathode material, halide solid electrolyte and conductive agent described in the above technical solution.
[0049] In this invention, the preferred mass ratio of the lithium-rich manganese-based cathode material, the halide solid electrolyte, and the conductive agent is 30:20:2.5.
[0050] In this invention, the halide solid electrolyte comprises Li3InCl6; the conductive agent preferably comprises VGCF (vapor-grown carbon fiber).
[0051] The present invention does not impose any particular limitation on the specific preparation method of the composite positive electrode, and any method known to those skilled in the art can be used, preferably in an argon atmosphere glove box.
[0052] In this invention, the environmental parameters of the argon atmosphere glove box are preferably: H2O < 0.01 ppm, O2 < 0.01 ppm.
[0053] The present invention also provides a solid-state battery, comprising the composite positive electrode, sulfide solid electrolyte, and negative electrode described in the above technical solution.
[0054] In this invention, the sulfide solid electrolyte preferably includes Li6PS5Cl.
[0055] In this invention, the negative electrode preferably comprises an indium sheet and a lithium sheet, wherein the thickness of the indium sheet is preferably 0.1 mm and the thickness of the lithium sheet is preferably 0.1 mm.
[0056] The present invention also provides a method for assembling a solid-state battery, preferably carried out in an argon atmosphere glove box, specifically including the following steps: Preferably, the sulfide solid electrolyte and the composite positive electrode are weighed in sequence, and then loaded into the mold layer by layer in the order of sulfide solid electrolyte → composite positive electrode and pressed into sheets. The pressing pressure of the sulfide solid electrolyte is preferably 3T, and the pressing pressure of the composite positive electrode is preferably 5T. The mass ratio of the sulfide solid electrolyte to the composite positive electrode is 100:6. Preferably, an indium sheet is first loaded, and then a lithium sheet is covered to obtain the negative electrode; Preferably, the assembled mold is placed in a pressure device and tightened by applying a torque of 10 N·m to obtain the solid-state battery.
[0057] The present invention does not impose any special limitations on the specific structure of the mold, and any solid-state battery test mold well known to those skilled in the art can be used.
[0058] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0059] Example 1 (1) 100.0g of precursor Ni 0.167 Co 0.167 Mn 0.666 (OH)2, 63.8g of lithium carbonate, and 1.6g of MoO3 were mixed in a high-speed mixer at 3000rpm for 30min. The mixture was first heated to 500℃ at 2℃ / min and held for 3h, then heated to 900℃ at 5℃ / min and held for 10h, and then heated to 1000℃ at 5℃ / min and held for 5h. The mixture was then cooled in the furnace to obtain lithium-rich manganese-based calcined powder, wherein the precursor:lithium carbonate (molar ratio) = 1:1.55, the molar amount of Mo accounts for 1% of the total molar amount of transition metal elements in the precursor, the precursor D50 = 1.5μm, and the lithium-rich manganese-based calcined powder D50 = 2.3μm. (2) Dissolve 0.200g NH4H2PO4 and 0.217g LiOH·H2O in 200mL deionized water and stir until clear. Heat to 40℃, add 100g lithium-rich manganese-based mono-calcined powder, stir for 2h to react fully, and then spray dry at 120℃. After drying, heat to 500℃ in air at 2℃ / min and keep for 6h to obtain lithium-rich manganese-based di-calcined powder. Mix 0.5g LiOH·H2O and 100g lithium-rich manganese-based di-calcined powder with a high-speed mixer at 3000rpm for 40min. Take 100mg and place it in a pressure vessel, apply 2T pressure, keep pressure for 3min, and then heat the pressure vessel to 500℃ in air at 2℃ / min and sinter for 6h. Grind the sintered material thoroughly and sieve it to collect the material, which is the lithium-rich manganese-based cathode material.
[0060] Example 2 (1) 100.0g of precursor Ni 0.167 Co 0.167 Mn 0.666(OH)2, 63.8g of lithium carbonate, 1.595g of MoO3, 0.410g of ZrO2, and 0.205g of NH4F were mixed in a high-speed mixer at 3000rpm for 30min. The mixture was first heated to 500℃ at 2℃ / min and held for 3h, then heated to 900℃ at 5℃ / min and held for 10h, and then heated to 1000℃ at 5℃ / min and held for 5h. The mixture was then cooled in the furnace to obtain lithium-rich manganese-based monocalcined powder. The precursor: lithium carbonate (molar ratio) = 1:1.55, the molar amount of Mo accounts for 1% of the total molar amount of transition metal elements in the precursor, the molar amount of Zr accounts for 0.3% of the total molar amount of transition metal elements in the precursor, the molar amount of F accounts for 0.5% of the total molar amount of transition metal elements in the precursor, the precursor D50 = 1.5μm, and the lithium-rich manganese-based monocalcined powder D50 = 2.3μm. (2) Same as step (2) in Example 1.
[0061] Example 3 (1) Same as step (1) in Example 2; (2) Dissolve 0.221g NH4VO3 and 0.079g LiOH·H2O in 200mL deionized water and stir until clear. Heat to 40℃, add 100g lithium-rich manganese-based mono-calcined powder, stir for 2h to react fully, spray dry at 120℃, and after drying, heat to 500℃ in air at 2℃ / min and keep for 6h to obtain lithium-rich manganese-based di-calcined powder. Mix 0.5g LiOH·H2O with 100g lithium-rich manganese-based di-calcined powder in a high-speed mixer at 3000rpm for 40min, take 100mg and put it into a pressure vessel, apply 2T pressure, keep pressure for 3min, heat the pressure vessel in air at 2℃ / min to 500℃ and sinter for 6h. Grind the sintered material thoroughly and sieve it to collect the material, which is the lithium-rich manganese-based cathode material.
[0062] Example 4 (1) Same as step (1) in Example 2; (2) Add 150 mL of deionized water to 0.445 g of silica sol (30% content), stir continuously, and heat to 40 °C. Dissolve 0.187 g of LiOH·H2O in 50 mL of deionized water and stir until clear. Add the LiOH·H2O aqueous solution dropwise to the silica sol at 2 mL / min. After stirring at this temperature for 2 h, add 100 g of lithium-rich manganese-based calcined powder and continue stirring for 2 h to allow the reaction to proceed fully. Then, spray dry at 120 °C. After the reaction is complete, dry in air at 2 °C / min. The temperature was raised to 650℃ and held for 6 hours to obtain lithium-rich manganese-based dicalcined powder. 0.5g LiOH·H2O and 100g lithium-rich manganese-based dicalcined powder were mixed in a high-speed mixer at 3000rpm for 40 minutes. 100mg of the mixture was placed in a pressure vessel, and a pressure of 2T was applied. After holding the pressure for 3 minutes, the pressure vessel was heated to 500℃ at 2℃ / min in an air atmosphere and sintered for 6 hours. The sintered material was thoroughly ground and sieved to collect the material, which is the lithium-rich manganese-based cathode material.
[0063] Example 5 (1) Same as step (1) in Example 2; (2) Dissolve 0.200g NH4H2PO4 and 0.217g LiOH·H2O in 200mL deionized water and stir until clear. Heat to 40℃, add 100g lithium-rich manganese-based mono-calcined powder, stir for 2h to react fully, and then spray dry at 120℃. After drying, heat to 500℃ in air at 2℃ / min and keep for 6h to obtain lithium-rich manganese-based di-calcined powder. Mix 0.5g LiOH·H2O and 100g lithium-rich manganese-based di-calcined powder with a high-speed mixer at 3000rpm for 40min. Take 100mg and place it in a pressure vessel. Apply 5T pressure and keep for 3min. Then heat the pressure vessel in air at 2℃ / min to 500℃ and sinter for 6h. Grind the sintered material thoroughly and sieve it. Collect the material, which is the lithium-rich manganese-based cathode material.
[0064] Example 6 (1) 100.0g of precursor Ni 0.167 Co 0.167 Mn 0.666(OH)2, 63.8g of lithium carbonate, 3.190g of MoO3, 0.410g of ZrO2, and 0.205g of NH4F were mixed in a high-speed mixer at 3000rpm for 30min. The mixture was first heated to 500℃ at 2℃ / min and held for 3h, then heated to 900℃ at 5℃ / min and held for 10h, and then heated to 1000℃ at 5℃ / min and held for 5h. The mixture was then cooled in the furnace to obtain lithium-rich manganese-based monocalcined powder. The precursor: lithium carbonate (molar ratio) = 1:1.55, the molar amount of Mo accounts for 2% of the total molar amount of transition metal elements in the precursor, the molar amount of Zr accounts for 0.3% of the total molar amount of transition metal elements in the precursor, the molar amount of F accounts for 0.5% of the total molar amount of transition metal elements in the precursor, the precursor D50 = 1.5μm, and the lithium-rich manganese-based monocalcined powder D50 = 2.3μm. (2) Same as step (2) in Example 1.
[0065] Example 7 (1) Same as step 1 in Example 2 (2) Dissolve 0.500g NH4H2PO4 and 0.543g LiOH·H2O in 200mL deionized water and stir until clear. Heat to 40℃, add 100g lithium-rich manganese-based mono-calcined powder, stir for 2h to react fully, and then spray dry at 120℃. After drying, heat to 500℃ in air at 2℃ / min and keep for 6h to obtain lithium-rich manganese-based di-calcined powder. Mix 0.5g LiOH·H2O and 100g lithium-rich manganese-based di-calcined powder with a high-speed mixer at 3000rpm for 40min. Take 100mg and place it in a pressure vessel, apply 2T pressure, keep pressure for 3min, and then heat the pressure vessel to 500℃ in air at 2℃ / min and sinter for 6h. Grind the sintered material thoroughly and sieve it to collect the material, which is the lithium-rich manganese-based cathode material.
[0066] Example 8 (1) Same as step 1 in Example 2 (2) Dissolve 0.200g NH4H2PO4 and 0.217g LiOH·H2O in 200mL deionized water and stir until clear. Heat to 40℃, add 100g lithium-rich manganese-based mono-calcined powder, stir for 2h to fully react, and then spray dry at 120℃. After drying, heat to 550℃ in air at 2℃ / min and keep for 6h to obtain lithium-rich manganese-based di-calcined powder. Mix 0.5g LiOH·H2O and 100g lithium-rich manganese-based di-calcined powder with a high-speed mixer at 3000rpm for 40min. Take 100mg and place it in a pressure vessel, apply 2T pressure, and keep pressurized for 3min. Then heat the pressure vessel in air at 2℃ / min to 550℃ and sinter for 6h. Grind the sintered material thoroughly and sieve it to collect the material, which is the lithium-rich manganese-based cathode material.
[0067] Comparative Example 1 (1) Same as step (1) in Example 1; (2) Mix 0.5g LiOH·H2O with 100g lithium-rich manganese-based sintered powder using a high-speed mixer at 3000rpm for 40min. Then, take 100mg and place it in a pressure container. Apply 2T pressure and hold the pressure for 3min. Then, sinter the pressure container at 500℃ in an air atmosphere. After sintering, grind the material thoroughly and sieve it. Collect the material, which is the lithium-rich manganese-based cathode material.
[0068] Comparative Example 2 (1) Same as step (1) in Example 2; (2) Take 100mg of lithium-rich manganese-based sintered powder and put it into a pressure container. Apply 2T pressure and hold for 3 minutes. Then, sinter the pressure container at 500℃ in air atmosphere. After sintering, grind the material thoroughly and sieve it. Collect the material, which is the lithium-rich manganese-based cathode material.
[0069] Comparative Example 3 (1) Same as step (1) in Example 2; (2) Dissolve 0.200g NH4H2PO4 and 0.217g LiOH·H2O in 200mL deionized water and stir until clear. Heat to 40℃, add 100g lithium-rich manganese-based sintered powder, stir for 2h to fully react, spray dry at 120℃, and after the reaction is complete, heat to 500℃ in air at 2℃ / min and keep for 6h. Grind the sintered material thoroughly and sieve it. Collect the material, which is the lithium-rich manganese-based cathode material.
[0070] Comparative Example 4 (1) 100.0g of precursor Ni 0.167 Co 0.167 Mn 0.666 (OH)2 and 63.8g of lithium carbonate were mixed in a high-speed mixer at 3000rpm for 30min. The mixture was first heated to 500℃ at 2℃ / min and held for 3h, then heated to 900℃ at 5℃ / min and held for 10h, and then heated to 1000℃ at 5℃ / min and held for 5h. The mixture was then cooled in the furnace to obtain lithium-rich manganese-based monazite powder, wherein the precursor:lithium carbonate (molar ratio) = 1:1.55, the precursor D50 = 1.5μm, and the lithium-rich manganese-based monazite powder D50 = 2.3μm. (2) Same as step (2) in Example 1.
[0071] Test Example 1 The lithium-rich manganese-based cathode materials obtained in Examples 1-5 and Comparative Examples 1-4 were respectively placed in a mortar with a halide solid electrolyte (Li3InCl6) and VGCF (vapor-grown carbon fiber) at a mass ratio of 30:20:2.5 and thoroughly ground and mixed. Lithium and indium sheets with a thickness of 0.1 mm were then cut into circular sheets using Φ6 mm and Φ9 mm circular punches, respectively, for later use. The entire process was carried out in an argon atmosphere glove box, with environmental parameters controlled as follows: H2O < 0.01 ppm, O3 < 0.01 ppm.
[0072] Weigh out 100 mg of sulfide solid electrolyte (Li6PS5Cl) and 6 mg of composite cathode in sequence. Place them layer by layer into the mold and press them into sheets, following the order of "sulfide → composite cathode". The pressing pressures for each layer are 3T and 5T, respectively. First, install the indium sheet on the negative electrode side, then cover it with the lithium sheet. Place the assembled mold in a pressurizing device and apply a torque of 10 N·m for tightening.
[0073] The electrochemical performance was tested using a constant current charge-discharge mode with a voltage range of 1.4 to 4.2 V at a rate of 0.1 C and a temperature of 25 °C. The results are shown in Table 1.
[0074] Table 1 Performance Test Results
[0075] As shown in Table 1, the discharge capacity of the lithium-rich manganese-based cathode materials in Examples 1-5 is 267.8-274.8 mAh / g, the initial coulombic efficiency is 87.5%-90.8%, and the 100-cycle retention rate is 91.5%-94.9%. The discharge capacity of Comparative Example 1 (without the coating layer) drops to 248.6 mAh / g, Comparative Example 2 (without the coating layer and binder) has a discharge capacity of only 227.9 mAh / g and a cycle retention rate of only 89.9%, Comparative Example 3 (without pressure sintering) has a discharge capacity of only 223.6 mAh / g and a cycle retention rate of only 89.0%, and Comparative Example 4 (without doping) has a discharge capacity of only 213.9 mAh / g and a cycle retention rate of only 88.4%. This demonstrates that the present invention, through a three-step synergistic process of "one-step doping - liquid phase coating - pressure sintering," enables the obtained lithium-rich manganese-based cathode material to possess high capacity, high rate capability, and long cycle performance in solid-state batteries.
[0076] Figure 1 The following are charge-discharge curves of samples from Examples 1 and 3, and Comparative Examples 1-4 at 0.1C; from Figure 1 It can be seen that the discharge specific capacity of Examples 1 and 3 is significantly improved.
[0077] Figure 2 The graphs show the specific capacity retention rates of the samples in Examples 1 and 3, and Comparative Examples 1-4 at 1C discharge. Figure 2It can be seen that the cycle retention rate of Examples 1 and 3 is significantly improved.
[0078] Figure 3 SEM image of the sample in Example 1; Figure 4 The SEM images of the samples in Comparative Example 3 show that grain boundaries were formed in Example 1, while in Comparative Example 3, a single primary particle was formed, with obvious differences in morphology.
[0079] In summary, this invention simultaneously retains the structural stability advantages of single-crystal materials while solving the problems of difficult activation and poor interfacial contact. A single-crystal matrix is prepared through a first sintering process to stabilize the single-crystal structure. A coating agent is uniformly loaded onto the surface of the single-crystal particles via spray drying, followed by a second sintering to form a coating layer, improving the interfacial ionic conductivity and solid-solid contact. Finally, LiOH is added as a binder, and pressure treatment and a third sintering cause grain boundaries to form between the single-crystal particles, agglomerating them into secondary particles, increasing Li+ diffusion channels and shortening the diffusion distance, thereby effectively activating the Li2MnO3 phase. Ultimately, the material significantly improves discharge specific capacity, cycle stability, and rate performance while retaining the stability of the single-crystal structure. This invention uses Mo... 6+ 、Nb 5+ W 6+ Ta 5+ High-valence, large-radius cations are used as dopants for bulk doping, and sintering is performed to form a single crystal morphology. - Anions replace O sites and transition metal sites in the crystal lattice, thereby improving lattice stability and thus improving the material's cycle retention rate. In this invention, lithium-rich manganese-based cathode material is combined with halide solid electrolyte and used at the cathode end. This combination can protect the structural stability of the lithium-rich manganese-based cathode material under high voltage. The electrolyte is a sulfide solid electrolyte. The halide on the cathode side and the sulfide on the electrolyte side work together to reduce the influence of the space charge layer, thereby obtaining a higher discharge specific capacity.
[0080] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a lithium-rich manganese-based cathode material, characterized in that, Includes the following steps: The precursor, lithium salt, and dopant are mixed and then subjected to a first sintering to obtain lithium-rich manganese-based sintered powder; the dopant includes one or more of ZrO2, TiO2, Al2O3, MgO, Co3O4, MoO3, Nb2O5, WO3, Ta2O5, NH4F, LiPO3, and Li2SO4. The lithium-rich manganese-based sintered powder and the coating agent are mixed and then spray-dried and sintered sequentially to obtain lithium-rich manganese-based bis-sintered powder; the coating agent includes a fast ion conductor material. The lithium-rich manganese-based sintered powder and LiOH were mixed and then subjected to pressure treatment and a third sintering process to obtain the lithium-rich manganese-based cathode material.
2. The preparation method according to claim 1, characterized in that, The dopant element in the dopant includes one or more of Zr, Ti, Al, Mg, Co, Mo, Nb, W, Ta, F, P and S, and the molar amount of each dopant element in the dopant independently accounts for 0.03 to 3% of the total molar amount of transition metal elements in the precursor.
3. The preparation method according to claim 1, characterized in that, The first sintering includes a first stage sintering, a second stage sintering and a third stage sintering performed sequentially. The temperature of the first stage sintering is 450~550℃ and the holding time is 3~6h. The temperature of the second stage sintering is 800~950℃ and the holding time is 8~12h. The temperature of the third stage sintering is 1000~1100℃ and the holding time is 3~6h.
4. The preparation method according to claim 1, characterized in that, The fast ion conductor material is a mixture of NH4H2PO4 and LiOH, a mixture of SiO2 and LiOH, or a mixture of NH4VO3 and LiOH; the amount of coating agent added is 0.05~1% of the mass of the lithium-rich manganese-based sintered powder; the spray drying temperature is 110~130℃; the second sintering temperature is 500~650℃, and the holding time is 4~7h.
5. The preparation method according to claim 1, characterized in that, The mass ratio of the lithium-rich manganese-based sintered powder to LiOH is 150~200:1; the pressure of the pressurization treatment is 2~5T, and the holding time is 2~5min; the temperature of the third sintering is 500~600℃, and the holding time is 4~7h.
6. The preparation method according to claim 1, characterized in that, The precursor has the general formula Mn x M y (OH)2, wherein 0.5 < x < 1, 0 < y < 0.5, x + y = 1, and M is Ni and / or Co; the molar ratio of the precursor to the lithium salt is 1:1.3 to 1:1.6, and the molar ratio is calculated based on the total molar amount of transition metal elements in the precursor and the molar amount of lithium elements in the lithium salt.
7. The lithium-rich manganese-based cathode material prepared by the preparation method according to any one of claims 1 to 6.
8. The application of the lithium-rich manganese-based cathode material according to claim 7 in solid-state batteries.
9. A composite positive electrode, characterized in that, It comprises the lithium-rich manganese-based cathode material as described in claim 7, a halide solid electrolyte, and a conductive agent, wherein the halide solid electrolyte comprises Li3InCl6.
10. A solid-state battery, characterized in that, It comprises the composite positive electrode, sulfide solid electrolyte, and negative electrode as described in claim 9, wherein the sulfide solid electrolyte comprises Li6PS5Cl.
